A Study on Pre and Post Merger Impact of PNB. - Mohan Kalyani, Mandar; Tekade, Atul (Journal of Neonatal Surgery, 2025)
The study investigates the impact of the merger on Punjab National Bank (PNB) by analysing both pre-merger and post-merger effects on its financial performance, operational efficiency, and overall market positioning. Focusing on the strategic, financial, and operational outcomes, the research explores the transformation of PNB after merging with its counterpart and assesses how these changes have shaped the bank's growth trajectory. The analysis includes a review of key performance indicators such as profitability, liquidity, asset management, and customer satisfaction. By evaluating the effectiveness of the integration process, the research highlights the challenges and opportunities faced by the bank in adapting to the merged entity's new structure. Additionally, the study explores the regulatory and management frameworks that have guided the transition, while considering the broader impact of such mergers on the banking sector. Insights from this research can serve as a reference for understanding the dynamics of mergers in the banking industry and the strategies that contribute to long-term success. This study contributes to the growing body of knowledge on corporate mergers and provides valuable lessons for stakeholders involved in future merger transactions.